Modelo Experimental de Deficiência de Tiamina Induzida por Amprólio em Camundongos. - Moraes, Juliana Oliveira (2023)
Neurological diseases are quite varied and have a great economic impact on livestock. Central nervous system (CNS) disorders may be caused by various etiologic agents, such as biological agents and by metabolic disorders. In this case, we highlight the polioencephalomalacia (PEM) triggered by thiamine deficiency (vitamin B1). PEM has been described in several regions of Brazil, involving cattle, sheep and goats. However, thiamine deficiency is important also for carnivores (Chastek's palsy) and humans (Wernicke disease and Wernicke-Korsakoff syndrome). The CNS regions involved in PEM are varied and contradictory, but are affected from cortical areas to deep regions such as the midbrain and thalamus. At these sites, there is typically neuronal degeneration and necrosis, with adjacent involvement of astrocytic and inflammatory changes. Little is known about the molecular and cellular mechanisms of degeneration and death of neurons. However, it is considered that the process related to thiamine deficiency is initiated by metabolic defects in the mitochondria with consequent establishment of oxidative stress. In the present work, we aimed to determine different parameters related to thiamine deficiency in the CNS in an in vivo model to evaluate the occurrence of cell death and the molecular mechanisms involved, association of behavioral changes and the design of efficient neuroprotective strategies, characterizing the CNS areas involved in thiamine deficiency-induced degeneration. The model of dietary deficiency in combination with injections of the thiamine antagonist, amprolium, was used in the present study. The animals were treated for 15 or 20 days and divided into 6 treatment groups: control (cont), amprolium (Amp), amprolium and Trolox® (Amp+Tr), amprolium and DMSO (Amp+Dmso), Trolox® (Tr) and DMSO (Dmso). Mice subjected to the thiamine deficiency model (Amp) exhibited a significant reduction in body weight gain after 15 and 20 days of treatment. The histopathological analysis revealed in the Amp group, centrolobular hepatic steatosis at 15-day and diffuse hepatic steatosis when treated for 20 days, in addition to moderate proteinuria. Trolox® and DMSO markedly attenuated steatosis (Amp+Tr and Amp+Dmso groups). No histological changes were observed in the CNS within 15 or 20 days of treatment. However, the cellular viability of the cerebral cortex significantly reduced in the Amp group after 20 days of treatment; which effect was reversed in the Amp+Tr and Amp+Dmso groups. In addition, deficient animals (Amp) presented behavioral changes such as reduction in ambulation and exploratory activities and in motor coordination and, interestingly, Trolox® and DMSO attenuated these effects. These data suggest that in the model of thiamine deficiency with amprolium the animals develop neurological and metabolic alterations, associated with oxidative stress and possibly inflammation. In addition, the model proves feasible for the study of vitamin deficiency with the establishment of a gradual progressive process, without being markedly aggressive, as in the classic model of pyrithiamine.